Reading strategies of a specialised rhetorical genre: The case of Law - Ariffin, Adlina (IIUM Press, 2017)
One of the most fundamental skills in the quest for knowledge is reading. Its importance is clearly illustrated in the first revelation or words of communication between Allah SNW with our beloved Prophet Muhammad SAW. These words – Surah Al Alaq (verses 1-5) – mainly comprise an instruction from Our Maker to mankind to explore the wealth and depth of knowledge in order to liberate oneself from the shackles of ignorance to the freedom of enlightenment. Hence, the knowledge that is gained will eventually bring man closer to the Most Bountiful One with a clear acknowledgement that all knowledge belongs to Him. Thus, the main purpose of this book is to share a research that focuses on the topic of reading by looking into the cognitive abilities in the reading of a specialised genre which is case law or legal case. The ability to read legal cases is one of the most essential skills for law students to be successful in their discipline. It is particularly fundamental since case law is one of the main sources of law. However, the most common assumption is that students would have possessed this skill when they enrol in a law school. This attitudinal fallacy is referred to as ‘skills deployment assumption’ (Stratman, 1990). Thus, this research attempted to explore the quintessential traits in the reading of legal cases among law students in one of the local universities in Malaysia. The main aims of the study was to unearth the reading strategies employed by law students and legal professionals in reading cases as well as identify similar and different reading strategies used. Data were collected via think-aloud protocol, retrospective interview and researcher’s observation. The findings revealed the differences in utilizing the case reading strategies between the different respondents and highlighted distinctive characteristics of strategic readers of legal cases such as the ability to employ varied reading strategies, establish context of the case, connect to previous experiences etc. This study has crucial implications on the teaching of case reading in legal education particularly to the curriculum designers, material developers, ESP instructors, legal educators and law students.